The megalopal stage of the hydrothermal vent crab Austinograea rodriguezensis Tsuchida & Hashimoto, 2002 (Decapoda: Bythograeidae): a morphological description based on CLSM images - Demidow, Olga; Kihara, Terue C.; Arbizu, Pedro Martínez; Clark, Paul F. (Zootaxa, 2021)
The Bythograeidae is unique amongst brachyuran crab taxa as it is the only family where all 6 genera and 16 species are endemic to hydrothermal vents. During the research conducted by German Federal Institute for Geosciences and Natural Resources to identify inactive polymetallic sulphide deposits along Central and Southeast Indian Ridges, the INDEX project collected from hydrothermal vent fields 6 Bythograeidae megalopae. Entire specimens and dissected appendages were stained, mounted on slides and examined using Light Microscopy and Confocal Laser Scanning Microscopy. Additional molecular analysis using mtCOI confirmed the identification of the specimens as Austinograea rodriguezensis Tsuchida & Hashimoto, 2002. The megalopal stage of A. rodriguezensis shows similarities and distinctions between the characters of two other bythograeid megalopae, Bythograea thermydron Williams, 1980, and B. microps Saint Laurent, 1984. Unlike other brachyuran megalopae, B. thermydron and A. rodriguezensis lack long serrate setae and stout serrate spines on the dactylus of the fifth pereiopod. In both species no coxal spines on the pereiopods were observed. The elliptical carapace of B. thermydron is broader than long vs longitudinally rectangular in A. rodriguezensis. This carapace shape resembles B. microps more than B. thermydron, however, the dorsal surface of B. microps carapace is densely covered in short setae vs only covered with short setae on the anterior 1/4 and the posterior 1/6 length of carapace in A. rodriguezensis. Furthermore, the amount of plumose natatory setae on the pleopods in B. microps is in total larger and more variable, than in A. rodriguezensis. Bythograeid megalopae seem quite generalized and miss specific features that reveal them distinctively as endemic vent crab. A distinction from other species is possible by observing the unique combinations of certain characters. This is the first megalopal stage description of Austinograea and the fourth within the Bythograeidae.